City Charter and Revised Ordinances of the City of Fall River 158 (1887) - (:unkn) unknown (My University, 1887)
Ordinance so the City of Fall River, Streets Use. Revised Ordinance. Discharge of Firearms. § 20: No person shall, except in the performance of some legal duty, discharge any gun, pistol or firearm in any street or public place, or within fifty rods of any dwelling house.
Keywords: DISCHARGE